A sociological approach to the concept of God amongst Iranian youth - Safa, Mina (HTS teologiese studies, 2011)
One of the most fundamental concepts in Sociology of Religion, the concept of God, was emphasised in this article. Although the God concept is not the same as the transcendental existence of God, it is this concept that is the most fundamental social construct in the entire history of world religions. The aim of this article was the conceptual reconstruction of God amongst the youth of Iran, who may be free from a theological approach. This article aimed to examine the God concept in the ‘epistemological’, ‘emotional’ and ‘social action’ domains. The Iranian society is in transition, faced with delusion about the traditional and modern belief systems, and multiplicity of interpretations and new presentation of One God Allah. A spectrum of these plural presentations of God embodies micro and macro social levels. Some of the most important of these concepts are: individual and personal concept of God, the God in family, in educational system, in religious rituals, and the dominant concept in the society.